L’art, l’architecture et l’espace public à la Villeneuve de Grenoble : l’utopie collective à l’œuvre ou l’échec d’une création partagée ? - Sibylle Le Vot (In Situ)
Celebrated for its concerted action promoting commissioned artworks, the city of Grenoble was during the Sixties a pioneer particularly known for its integration of fine arts within the urban space and into the everyday life. After the first french Symposium of sculpture in 1967, creation became a collective action and was put to test during the making of the new architectural and urban neighbourhood of the “Villeneuve” de Grenoble. Archetype of a collaborative work, the realization conceived by the Atelier d’urbanisme et d’architecture (AUA) is still the singular example of a multidisciplinary work. It is therefore not surprising that among the fifteen artworks exhibited in the open air – such as the works of the coopérative des Malassis, Guy de Rougemont and Klaus Schultze –, several show an attempt to elaborate beforehand a reflection shared by architects and artists